Major Pharmacy Practice Challenge for India: Irrational Fixed Dose Combinations - Patel, Kunjal; Patel, Prachie; Sekar, M. Chandra (Indian Journal of Pharmacy Practice)
During the advanced pharmacy practice rotation in India in the winter of 2017, The University of Findlay Pharmacy students observed the availability and sale of large number of fixed dose combinations and many of those combinations made no pharmacological sense. While availability of “irrational combinations” in Indian market is old news, what is new in this report is our observation that unless pharmacy practitioners in India are able to eliminate these proliferation of irrational combinations from the market–it will suffocate the growth of the nascent field of pharmacy practice that is being promoted by awarding doctor of pharmacy degree at the Indian educational institutions.
Keywords: Fixed dose combination; Pharmacy Practice; India; Clinical Pharmacy; Barrier; Pharm D.